2013
DOI: 10.1002/jgra.50200
|View full text |Cite
|
Sign up to set email alerts
|

Lower thermospheric‐enhanced sodium layers observed at low latitude and possible formation: Case studies

Abstract: [1] We report two lower thermospheric-enhanced sodium layer (TeSL) cases observed at a low-latitude station, Lijiang, China (26.7°N, 100.0°E), on 10 March and 10 April 2012, respectively. The TeSLs in the two cases were located at altitudes near 122 and 112 km, respectively. In addition, strong sporadic sodium layers (SSLs) near 100 km accompanied the TeSL observed on 10 March 2012. Both the TeSLs and SSLs exhibited tidal-induced downward motion. The adjacent ground-based and space-borne ionospheric radio obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 38 publications
5
51
0
Order By: Relevance
“…With the development of TeSLs over time, RO measurements accordingly show complex E s . Actually, Xue et al (2013) also reported an example showing that the lidar observes TeSLs associated with simultaneous double peaks of SNR made by colocated RO events from TerraSAR-X. According to wind shear theory, at lower (upper) altitudes, the zonal (meridional) wind will dominate the shear due to the altitude variations of the ion-neutral collision frequency regarding the ion gyrofrequency ratio.…”
Section: Multiple E S Layers In One Profilementioning
confidence: 96%
“…With the development of TeSLs over time, RO measurements accordingly show complex E s . Actually, Xue et al (2013) also reported an example showing that the lidar observes TeSLs associated with simultaneous double peaks of SNR made by colocated RO events from TerraSAR-X. According to wind shear theory, at lower (upper) altitudes, the zonal (meridional) wind will dominate the shear due to the altitude variations of the ion-neutral collision frequency regarding the ion gyrofrequency ratio.…”
Section: Multiple E S Layers In One Profilementioning
confidence: 96%
“…In this context, it is also to be noted that high altitude sporadic metal layers (or high altitude metal layers) have been reported from several observational sites (e.g. Friedman et al 2013, Höffner andFriedman 2004;Chu et al 2011;Xue et al 2013). Gao and Mathews (2014a,b) and references therein report on high altitude radar and optical meteors indicative of sputtering as a source of metal ions above the traditional meteor zone.…”
Section: Introductionmentioning
confidence: 73%
“…Several other studies have also indicated that gravity waves are vulnerable to breaking in the mesopause region (80-105 km) owing to the temperature inversion layer [Hauchecorne et al, 1987;Meriwether et al, 1998;Gardner et al, 2002;Williams et al, 2002]. Clemesha et al, 1999;Friedman et al, 2000;Dou et al, 2010;Xue et al, 2013]. And a less pronounced link, or absence of a link, between Es and SSL is observed below 95 km [Hansen and Von Zahn, 1990].…”
Section: Introductionmentioning
confidence: 94%
“…Several studies Clemesha et al, 1999;Williams et al, 2007;Dou et al, 2010;Xue et al, 2013] have shown that SSLs are associated with sporadic E (Es) layers. Cox and Plane [1998] reported that Na + can …”
Section: Sporadic E Layer Mechanismmentioning
confidence: 99%